Evaluation of the functional gastrointestinal diseases concept from standpoints of Rome IV (2016) diagnostic criteria (review) - D. N. Andreyev; A. V. Zaborovsky; A. S. Trukhmanov; I. V. Mayev; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2018)
Aim of review. To present the modern concept of functional gastrointestinal diseases (FGID) and to analyze the basic clinically relevant changes made in Rome IV criteria (2016) in comparison to the previous edition. Summary. According to the due definition that was proposed by the Rome IV advisory council, FGID are the brain-gut axis interaction disorders. It was proposed to exclude the term «functional» from the definition. The new nosological entities with known causative factor (opioid-induced gastrointestinal hyperalgesia, opioidinduced constipation, cannabinoid induced hyperemesis syndrome), hypersensitive reflux syndrome, nausea and vomiting syndrome (that encompasses previously separate nosological forms: chronic idiopathic nausea and functional vomiting) were added to the new version of the classification. In the new edition of Rome criteria the management approach to patients with sphincter of Oddi dysfunction is specified, along with diagnostic criteria of functional dyspepsia and irritable bowel syndrome. Conclusion. The classification of FGID is revised in updated Rome criteria, diagnostic features of several nosological entities were specified.